2020
DOI: 10.1039/d0tc00773k
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast spectroscopic investigation of the effect of solvent additives on charge photogeneration and recombination dynamics in non-fullerene organic photovoltaic blends

Abstract: The effects of DIO and CN additives on the neat and PBDB-TF:IT-4F blend film morphologies and the related ultrafast photophysical processes are studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…[ 138,143,173 ] Indeed, owing to the negligible geminate recombination losses in high performance NFA OSCs, we expect the geminate T 1 formation pathway to be insignificant. [ 10,121,174 ] However, there have been a number of reports where nongeminate T 1 formation in NFA OSCs has been observed, [ 165,175,176 ] confirming that this potential loss pathway is still active. As the NFA OSCs in these studies exhibited good performance (PCEs ≈11–12%), it is apparent that T 1 formation does not preclude efficient photocurrent generation, consistent with the observations of Karuthedath et al.…”
Section: Device Performancementioning
confidence: 99%
“…[ 138,143,173 ] Indeed, owing to the negligible geminate recombination losses in high performance NFA OSCs, we expect the geminate T 1 formation pathway to be insignificant. [ 10,121,174 ] However, there have been a number of reports where nongeminate T 1 formation in NFA OSCs has been observed, [ 165,175,176 ] confirming that this potential loss pathway is still active. As the NFA OSCs in these studies exhibited good performance (PCEs ≈11–12%), it is apparent that T 1 formation does not preclude efficient photocurrent generation, consistent with the observations of Karuthedath et al.…”
Section: Device Performancementioning
confidence: 99%
“…Thus, we refer to the process that depletes the intensity of the diagonal peak as “charge transfer”, keeping in mind that it could also be energy transfer. Charge transfer is known to be highly efficient ,, in these photovoltaic films and has been previously measured to be ultrafast. ,,, Thus, one likely reason for faster dynamics is electron transfer from PM6 excitons to the acceptor molecules.…”
mentioning
confidence: 99%
“…25 Yang et al found that use of solvent additives in preparation of the bulk heterojunctions can suppress recombination losses. 35 A more advanced form of TA spectroscopy, ultrafast twodimensional electronic spectroscopy (2DES), probes both structures, and dynamics. By measuring 2D lineshapes as a function of delay time, the magnitude and time scales of the fluctuations of the environment around the photogenerated excitons are measured, which are created by molecular differences in structure and their motions.…”
mentioning
confidence: 99%
See 2 more Smart Citations